1958
DOI: 10.1021/j150569a024
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium–Strontium Metal Phase System

Abstract: The calcium-strontium phase system has been investigated in the liquid and solid state over the entire range of compositions. The liquidus and_ solidus curves were determined by differential thermal analysis whereas the solid state equilibria were studied by X-ray diffraction methods. Complete miscibility in both the liquid and solid state were observed with a minimum in the liquidus-solidus at 78 ± 2 weight % strontium and at 738°. Calcium, strontium and all calcium-strontium alloys exist in three crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…For the Rietveld refinement of the Ca 8 (Al 0.9 Ni 0.1 ) 3 alloy, the structure models for the Ca 8 Al 3 , Ca and NiAl phases were, respectively, taken from the reported structures [4,8,9]. We initially assumed that Ni atoms randomly occupy the Al sites in the Ca 8 Al 3 phase.…”
Section: Resultsmentioning
confidence: 99%
“…For the Rietveld refinement of the Ca 8 (Al 0.9 Ni 0.1 ) 3 alloy, the structure models for the Ca 8 Al 3 , Ca and NiAl phases were, respectively, taken from the reported structures [4,8,9]. We initially assumed that Ni atoms randomly occupy the Al sites in the Ca 8 Al 3 phase.…”
Section: Resultsmentioning
confidence: 99%
“…Peterson and Fattore (Ref 20) suggested that a small amount of hydrogen induces the appearance of the c phase. Some researchers (Ref [21][22][23][24][25] suggested that this phase may be of hcp structure considering the allotropic transformation of pure Ca. In this work, the c phase is treated as a simple solution phase with hcp structure.…”
Section: The Li-h Binary Systemmentioning
confidence: 99%
“…Prior to applying the ternary SQSs to the Ca-Sr-Yb system, the mixing behavior of the fcc phase in its constitutive three binaries was investigated through eight-atom binary fcc SQSs at three different compositions, namely, x = 0.25, 0.5, 28,29 to evaluate interaction parameters in Eq. ͑4͒ for each binary.…”
Section: A Binary Special Quasirandom Structures For the Ca-sr-yb Symentioning
confidence: 99%